FATTY LIVER, NAFLD, MAFLD AND NASH A MENACE FAR BIGGER THAN ANTICIPATED: NEED FOR PRE-EMPTIVE DIAGNOSTICS: FATTY LIVER DISEASE SCREENING - KHAN, SIKANDAR HAYAT (Journal of Ayub Medical College Abbottabad, 2021)
Had liver a face to mirror itself, perhaps we could have avoided a lot of dietary abuse. While it’s not so a lot of yummy taste that the tongue relishes are passed down as permanent freckling to the metabolic factory. In medicine Non-Alcoholic Fatty Liver disease (NAFLD), and its synonyms like Fatty Liver Disease and Metabolic Associated Fatty Liver Disease (MAFLD) have emerged as one the commonest hepatic disorders. Excessive fat inside liver is a sign of multiple future diseases starting from liver damage itself, where Non-alcoholic Steatohepatitis (NASH) has been associated progress to cirrhosis and onward liver failure in 20% of patients in the developed world.1 The undesirable hepatic and visceral fat deposition has also been strongly shown to be associated with metabolic syndrome and some literature even narrated NAFLD as pre-diabetes.2 Next generational evidence-based medicine supplanted by nano diagnostics and molecular data has reshaped our understanding of hepatic fat accumulation and resulting complications compromising the human metabolic function. Alongside real-time insight into the fat related liver diseases through multiple biomarkers and integrated diagnostics, there emerges the possibility of tackling pathobiology with newer candidate therapeutics. The initial effects of hepatic fat accumulation may not be symptomatic, but possible signs of obesity and clinical evaluation do intake higher intake of refined carbohydrates and fat rich diets. However, we do interpret the benign to pathological transition as become apparent from hepatic steatosis to fibrosis with ill-fated suffering due to hepatocellular carcinoma (HCC). Provided basic understanding of the jigsaw puzzle between fat and liver’s misery the underlying mechanics at play seem to be differing and multiple. A recent study by Mann et al have identified few single nucleotide variants (SNVs) which could fast track NAFLD to adverse outcome associated NASH along with certain protective variants.3 Similarly, researchers through expression studies and various proteomic data have also been able to identify molecular signatures for development if NAFLD and NASH, allowing us to dissect the staged progression from simplistic steatosis to end-staged liver disease and HCC.4 While most Caucasian studies depict obesity to be the underlying cause of fatty liver to be associated with higher obesity indices like body mass index (BMI) waist to hip or height ratio. Asians and in specific South Eastern Asians have varied obesity deposition profiles, termed as Asian obesity paradox where individuals need not be apparently obese but still manage to accumulate excessive fat in liver along with complications including cirrhosis.5 Similarly, this pattern is non-obese NAFLD apart from progression to cirrhotic liver disease, has also been associated with subclinical atherosclerosis and various metabolic diseases.6 We have already highlighted unnecessary buildup of fat in hepatic tissue can possibly result in diabetes.2 Therefore, there is convincing data to suggest that appearance of NAFLD with or without obesity remains a key trigger to various hepatic and non-hepatic diseases including diabetes, metabolic syndrome, polycystic ovarian syndrome and certain adenocarcinomas.6,7 The aforementioned discussion suggests the trickledown effect from exuberance of food with less optimal exercise rate stays should be the mainstay of primary prevention. The early life hepatic steatosis, if screened through ultrasonography and serum ALT could intercept the vicious leading to magnitudes of patient load from metabolic diseases, adding quality to life years, amplifying national productivity, help reduce tons of financing due to reduced medical interventions including liver transplantation and will ward human kind from enormous sufferings and miseries. The current recommendations on screening for fatty liver disease remain controversial. The recommendations by North American Society for Paediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN) is to include ALT levels for screening fatty liver disease, while the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) suggests screening by using ultrasonography and serum ALT levels both.8 Alongside Asian Pacific Working Party for NAFLD, the Endocrine Society and Chinese Liver Disease Association also recommend screening for fatty liver disease albeit in different modes. The current understanding evident by prevailing practice in our region suggests an oblivious approach towards NAFLD screening in children adolescents and adults.9 The region hallmarked by rapidly urbanizing population with atypical visceral fat distribution and biostatistics depicting a concerning trend for increase in metabolic diseases with spectrum spanning from cirrhosis to diabetes, metabolic syndrome and list of adenocarcinomas needs attention of medical practitioners. While we may not be blessed with financial and medical resource to manage these cancers and life-long metabolic ailments and population being so naÃ¯ve and illiterate of incoming a strong suggestion is warranted to help reduce the productive life years metabolic ailments, which can be rooted out at the outset by timely screening and lifestyle modifications. There can be slogan for this No Room for Fat in Liver.